Topological transformation of LDH nanosheets to highly dispersed PtNiFe nanoalloys enhancing CO oxidation performance. Issue 27 (8th July 2020) - Ding, Junfang; Li, Liping; Wang, Ye; Li, Huixia; Yang, Min; Li, Guangshe
Abstract : Highly dispersed nanoalloys with a tailored metal–oxide interface are pivotal in developing advanced catalysts with superior performance for applications. Abstract : Highly dispersed nanoalloys with a tailored metal–oxide interface are pivotal in developing advanced catalysts with superior performance for applications. Herein, a series of highly dispersed Pt/NiFeAl nanoalloys on amorphous supports were successfully fabricated by a topological transformation of layered-double-hydroxide nanosheets. With increasing reduction temperature, samples Pt/NiFeAl- x ( x = reduction temperature) showed a progressive transformation from Pt/NiFeAl-LDH to a mixture (Pt, NiFe alloys, FeOy, and NiOy ) supported on amorphous Al2 O3, which eventually transformed to atomically dispersed PtNiFe alloys supported on amorphous Al2 O3 . Systematic sample characterization demonstrates that amorphous alumina-supported PtNiFe nanoalloys are merited by excellent redox ability, outstanding O2 activation ability, and moderate CO adsorption strength. When tested as catalysts for CO oxidation, all samples have demonstrated an apparent interfacial effect on catalytic performance, among which Pt/NiFeAl-600 shows a strikingly high CO oxidation activity at low-temperatures coupled with a broader operation temperature window ( i.e. CO conversion >99.0%, 100–400 °C). Such a topological transformation strategy has proven applicable for generating atomically dispersed nanoalloys on amorphous supports for catalytic applications.